Content Validity of HIT‐6 as a Measure of Headache Impact in People With Migraine: A Narrative Review. Issue 1 (6th December 2019) - Houts, Carrie R.; Wirth, R.J.; McGinley, James S.; Gwaltney, Chad; Kassel, Eric; Snapinn, Steven; Cady, Roger
Abstract : Background: The short‐form Headache Impact Test (HIT‐6) is a widely used patient‐reported outcome measure that assesses the negative effects of headaches on normal activity. It was developed using the general headache population and prior to the establishment of the now well‐accepted FDA patient‐reported guidance. Objective: The objective of this narrative review was to examine existing qualitative research in patients with migraine and headache, providing insight into the relevance and meaningfulness of HIT‐6 items to the lives of migraine patients. Methods: Articles were identified through database searches (National Library of Medicine and Google Scholar) and review of reference lists of candidate articles. Results: A total of 3227 articles were identified through database and hand searching. Of these, 12 contained patient‐ or expert‐generated qualitative information regarding headache patients' experience (8 specific to migraine [episodic and chronic] patients and 4 citing general headache patients). The combined publications described a total of 283 patient interviews. Overarching themes and specific information were identified that provide support of the relevance of content for each HIT‐6 item to migraine patients' lives. Identified effects of headaches on patients with migraine included limitations in daily activities, needing to lie down during headaches, feeling tired, being irritated by headaches, difficulty concentrating, and the experience of pain. Further, previous research specific to the HIT‐6 indicated that patients understood the instructions, items, and response scales as intended by the instrument authors. Conclusions: This narrative literature review demonstrates qualitative research support for the relevance of the items of the HIT‐6 in migraine patients, supporting its ongoing use in clinical migraine research and practice.